Eco-Linguistics in Indonesian Media: Language Construction of Environmental Issues in Digital News - Zamachari dofir (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
This study aims to reveal the linguistic constructions of environmental issues in the digital media Kompas.com through an ecolinguistic perspective. The focus lies on how language is used to frame ecological realities, particularly through dramatic, metaphorical, and technocratic expressions. The object of the research is news texts from Kompas.com covering environmental issues, especially floods, forest fires, deforestation, and air pollution. The study employed a qualitative design with a critical ecolinguistic discourse analysis approach. The data were drawn from news articles published between 2022 and 2024. Data collection techniques included documentation and critical reading, while data analysis followed Fairclough’s critical discourse analysis model focusing on text, discursive practice, and social practice. The findings indicate that Kompas.com’s linguistic constructions tend to frame the environment as a destructive threat, an aggressive actor, or merely a technical problem. The implications highlight the urgency of promoting more sustainable ecological narratives in the media that foster environmental awareness and encourage greater public participation in environmental protection.